Challenges Regarding Transition from Case-Based Learning to Problem-Based Learning: A Qualitative Study with Student Nurses. - Phage, Ramoipei J.; Molato, Boitumelo J.; Matsipane, Molekodi J. (Nursing Reports, 2023)
Background: The transition from case-based learning to problem-based learning can be challenging and may have negative effects on the academic, psychological, emotional, or social well-being of student nurses. As a result, this exposes student nurses to high failure rates, anxiety disorders, a loss of uniqueness, and fear of the unknown. However, student nurses employ different strategies aimed at overcoming challenges faced during this transition period. Methods: An exploratory, and descriptive research approach was used. A purposive non-probability sampling technique was used to select participants. Focus group discussions via Zoom video communication were used to collect data, which were analysed using Braun and Clarke's six steps of thematic analysis. Results: The following three themes emerged: challenges regarding facilitation, challenges regarding assessment, and strategies to overcome challenges. Conclusions: The study established that student nurses are faced with different challenges during the transition from one teaching strategy to another. Student nurses suggested strategies that could be used to overcome these challenges. However, these strategies are not enough and therefore more needs to be done to support and empower student nurses.